Concussion in the UK: a contemporary narrative review - Emma Toman; Valentina Di Pietro; Antonio Belli; Sam Hodgson; Max Riley; Richard Welbury (Trauma Surgery & Acute Care Open)
Concussion has been receiving an increasing amount of media exposure following several high-profile professional sports controversies and multimillion-dollar lawsuits. The potential life-changing sequalae of concussion and the rare, but devasting, second impact syndrome have also gained much attention. Despite this, our knowledge of the pathological processes involved is limited and often extrapolated from research into more severe brain injuries.As there is no objective diagnostic test for concussion. Relying on history and examination only, the diagnosis of concussion has become the rate-limiting step in widening research into the disease. Clinical study protocols therefore frequently exclude the most vulnerable groups of patients such as those with existing cognitive impairment, concurrent intoxication, mental health issues or learning difficulties.This up-to-date narrative review aims to summarize our current concussion knowledge and provides an insight into promising avenues for future research.